Ways of Applying the Competence of Developing Aesthetic Culture and Creativity in the Development of Musical Knowledge in Primary Grades (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article presents methods of how one of the 3 main competences accepted for applied sciences defined in the "National Curriculum" can be used in practice to develop the competence of aesthetic culture and creativity.